CHRONOLOGY OF NICCOLO MACHIAVELLI'S ANTHROPOLOGICAL PESSIMISM - Lapčević, Milivoje B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The point of the article is to determine and consider the Niccolo Machiavelli’s ideas about the human nature. N. Machiavelli believed that historical patterns repeat cyclically over the time. Therefore, the key to consideration hypotheses about the negative human nature, which is especially manifested in politics, was historical method. As the foundation of Machiavelli's theory is seen through a pessimistic view based on human nature, the genesis of this idea's development is revealed through chronology. The research focuses on several segments. First is presented the basic idea and assumption of human political nature in antiquity. The ideas of ancient thinkers are presented as an introduction to the thought of N. Machiavelli. A detailed account of the consideration of social life through the philosophical thought of Aristotle, shows the first ideas and explanation of the negative nature of people in politics. As the detailed historical method was the way of understanding N. Machiavelli's concretization of ancient ideas shows more clearly the way of thinking of anthropological pessimism. The Principe, as the key work N. Machiavelli's is considered through a comparative analysis with the rest of the written legacy. After determining the thought of N. Machicavelli the entire idea of anthropological pessimism is linked to human rights and the chronology that follows the development of mechanisms for the protection of this set of rights. New facts and understanding of anthropological pessimism are presented as an opportunity for better acquaintance, but also for better normalization of relations within the framework of functioning of the social community.
Keywords: anthropological pessimism, antiquity, Machiavelli, human rights, politics.